PROPOSAL FOR A SYSTEM OF ENVIRON MENTAL INFORMATION IN THE COLLECTION OF SOLID WASTED IN THE DISTRICT OF SAN LUIS, LIMA, PERU - Bardales, Julio (2016)
This paper proposes the Environmental Information System of the District of San Luis in Lima, with the objectives: the creation of an environmental database district of San Luis, and optimal routes, in which the best routes arises to minimize costs and maximize efficiency in the collection of solid waste segregated. Also, according to the analysis of economic evaluation conducted VAN 267235.12, an IRR of 34.37 % and Benefit / Cost 1.106 ratio was obtained with the alternative scenarios for increasing participation of 10, 20, 40, 80, and 100 %.